AKNOP, Budget Realization, and River Structure Performance in Flood Mitigation: A Quantitative Study of the Progo River Basin as Non-Military Defense Infrastructure - David Carlos Methlis Mone; Jupriyanto; Gregorius Henu Basworo (Indonesian Journal of Advanced Research, 2026)
River infrastructure sustains irrigation, flood control, and regional connectivity, yet its upkeep is often constrained by budgets that fall short of measured needs. This study examines how the Actual Operation and Maintenance Needs Index (AKNOP) value and budget realization relate to the physical condition of river structures across the Progo River Basin, and places that relationship within a non-military defense framework. A census of 88 structures was analyzed through rank regression once the normality assumption was violated. Both AKNOP value and budget realization significantly shaped structural condition, together explaining 87.1 percent of its variation. The negative coefficients trace back to volume-based cost estimation and urgency-driven budget allocation rather than wasteful spending, an interpretation corroborated by expert validation.